To What End: Machiavelli, Natural Law, and Politics - Rogers, Zachary D (URJ-UCCS: Undergraduate Research Journal at UCCS, 2016)
In the following article, the author critically analyzes Niccolo Machiavelli's theories of utilitarianism as set forth in his work The Prince. This paper discusses the utilitarianism and political expediency this text recommends, and the superiority of Natural Law Theory for creating a framework for political action.